Orally-Administered Caspase Inhibitor PF-03491390 Is Retained in the Liver for Prolonged Periods With Low Systemic Exposure, Exerting a Hepatoprotective Effect Against α-Fas-Induced Liver Injury in a Mouse Model - Yoshinobu Ueno; Takashi Ohmi; Mitsuko Yamamoto; Naoto Kato; Yukiko Moriguchi; Midori Kojima; Rieko Shimozono; Sachiko Suzuki; Tomomi Matsuura; Hiroyuki Eda (Journal of Pharmacological Sciences, 2007)
In a mouse model of α-Fas-induced acute liver injury, the orally-administered caspase inhibitor PF-03491390 (formerly named IDN-6556) was retained in the liver for prolonged periods with a low systemic exposure. Reductions in the elevated plasma levels of alanine aminotransferase (ALT) revealed that the retention of PF-03491390 in the liver exerted a hepatoprotective effect, even when pre-administered to mice 4 h before α-Fas insult. Prolonged retention of PF-03491390 in the liver after oral administration has the benefit of low systemic exposure, making this a beneficial agent for the treatment of liver diseases. Keywords:: caspase, Fas, alanine aminotransferase (ALT)